Association of Consumer Behavior to a Circular Economy: Assessing a Variety of Perceptions and its Correlation in Germany - Priatmojo, Widyasmoro (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
Complexity in the circular economy concept enforced the integration of disciplines and a holistic approach to engender the implementation. A breakdown to bring a circular economy project to a level of market presumably provides the contribution toward the circular economy prospect. Problem identification is a deficiency in consumer behavior discovery. The objective of the research is to discover the characteristics through demographic analysis as well as to assess the association of attitude and perception toward the circular economy objective. The case is specified in Germany since it introduced effective waste management regarding a cyclical process. The conceptual framework is a model of factors influencing decision-making issued by the European Commission and a model of the Tri-component attitude. The data analysis method is quantitative by adopting a method of Cross tabulation with Chi-Square and Structural Equation Modeling. The findings demonstrated low demand for a circular economy market, price and quality are the highest indicators while buying a product, old adulthood and female respondents tended to put more concern on waste issues, and an increase in willingness to spend more in finance on eco-friendly products positively would rise the intention of engaging in the social and environmental context. This observation is relevant for SDGs objectives.